Construction of GmNAC085 vector for future development of drought-tolerant crops - Xuan, Hoang Thi Lan; Thu, Nguyen Binh Anh; Phuc, Nguyen Bao Thien; Thao, Nguyen Phuong (Vietnam Journal of Biotechnology, 2018)
Various members of NAC transcription factor family have been shown to play important roles in regulating plant responses to abiotic stresses, such as drought, cold and salinity. Our previous research on differential expression patterns of twenty three soybean NAC genes (GmNACs) by realtime quantitative PCR suggested a correlation between inducible expression of GmNAC085 and the drought tolerance degree in DT51 and MTD720 soybean cultivars, which presented for the drought-tolerant and the drought-sensitive, respectively. Therefore, the gene has been proposed as a potential candidate for engineering in order to produce new varieties with better drought stress tolerance. However, functional studies of GmNAC085 should be carried out to identify how this transcriptional factor can contribute in the plant stress-responsive pathway. Herein, this paper presented that we have successfully developed a recombinant binary vector carrying full-length cDNA of GmNAC085 and expression of this gene is placed under the control of constitutive promoter CaMV 35S. The generated construct was firstly transformed into E.coli for sequencing the target gene and then the identified genuine construct was transformed into Agrobacterium tumefaciens. This can be used for plant transformation mediated by Agrobacterium in serving for GmNAC085 - related studies using in planta system such as the model plant Arabidopsis and also serving for the development of drought-tolerant crops by genetic engineering. Additionally, results from sequence alignment analysis revealed that GmNAC085s of DT51 and MTD720 had identical nucleotide sequence, thus supporting our hypothesis that difference in GmNAC085 gene expression levels, not the variation in GmNAC085 protein sequence or structure, might cause the difference in plant resistance degree to drought stress in these two soybean varieties